Pengaruh Motivasi, Kepuasan Kerja dan Disiplin Kerja terhadap Kinerja Karyawan pada PT. Japfa Comfeed Indonesia Tbk. Unit Padang - Lidya Martha; Riza Miawan Putra (JURNAL PUNDI, 2020)
ABSTRACTThe purpose of this study was to examine whether the effect of motivation, job satisfaction and work discipline on employee performance on PT. Japfa Comfeed Indonesia Tbk. Padang units. This study uses quantitave methods, the population in this study were 50 employees of the production departement at PT. Japfa Comfeed Indonesia Tbk. Padang Units. The sample technique used is saturated sampling technique, so that a sample of 50 people is obtained. Data retrieval is done by distributing questionnaires to the employees of PT. Japfa Comfeed Indonesia Tbk. Padang Units. The data analysis technique multiple regression. The result of the three variable tests show, motivation has a positive and significant effect on employee performance, job satisfaction has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance.Keywords : Motivation, Job Satisfaction, work discipline, employee performance.